Imaging protocols for the autopsy service in a time of pandemic emergency minimizing the contagion of SARS-CoV-2 expert government agents (Research, Society and Development, 2021)
Objective: To contribute to the construction of parameters of biosafety in order to protect government agents in the exercise of their investigative functions in the context of a pandemic, as well as to resolve clinical, pathological and possibly legal issues. Methodology: The development of an exploratory review study with a qualitative approach was defined. The methodological design was carried out on the platforms: PubMed and SciELO through the descriptors: Human identification, Radiology, Virtópsia and Autopsy. The exclusion criteria include articles with duplicate information or that do not have information related to the objectives of the study. For inclusion, materials published in Portuguese, English or Spanish were used and at the end 76 articles were obtained. Results and discussion: Conventional autopsy is the most common method for post-mortem investigation in humans. However, with the evolution of imaging methods and the current pandemic threatening the health of government agents, Virtópsia has shown itself to be the most promising way to remedy the dichotomy of occupational risk and legal benefit. Final considerations: In this article, the main advances in Forensic Radiology in the last 11 years were described, with regard to the use of ante and post mortem radiographs in the identification process. Among the various radiological techniques treated, the following stand out: radiographic techniques produced by radiology professionals with different assessments in the radiological area. The images produced are security methods with invasive manipulation and use of all PPE, suitable for the pandemic moment.